Characteristics of variability of morpho-physiological parameters of lesser duckweed (Lemna minor) under heavy metals cultivation - Zhyvitskaya, Alena P.; Sysa, Aliaksei G.; Butchenkov, Igor E.; Vlasenko, Evgenii K. (Journal of the Belarusian State University. Ecology, 2022)
It was shown scientifically substantiated the use of the lesser duckweed (Lemna minor L.) as a test object for environmental monitoring purposes when contaminated with copper (II), iron (II), lead and zinc cations. The influence of metal cations in the concentration range from 0.1 to 10.0 mg/l on the specific growth rate and dynamics of changes in the total area of leaf blades (fronds) of freshwater duckweed plants has been studied. It was shown that in the concentration range of Cu2+ and Fe2+ cations of 0.1-0.25 mg/ml, the growth rate of duckweed did not differ from control plants, while zinc and lead cations had a 17.3 % and 30 % inhibitory effect, respectively. Analysis of the curves of changes in the specific rate of algae growth in the concentration range of 0.5-2.5 mg/l showed that the effectiveness of the inhibitory effect on the growth of duckweed decreased in the series Zn2+ > Pb2+ > Fe2+ > Cu2+, which was also confirmed by data on the dynamics of the decrease in the average frond areas before and 7 days after cultivation. The results of the work show that the small duckweed (Lemna minor) can be used in bioindication measures regarding the content of elements of the group of heavy metals (copper (II), iron (II), lead and zinc) in water bodies.